7.18.25 - Ting, Phoebe Bei Shi (2018)
The subject of this Final Year Project Report is 7.18.25, a short 2D animated film by my team (Jolene Tan, Phoebe Ting and Hu Min Hao). The film is portrayed to have three different styles for each part, with the connection between the three shorts is only made at the end of the film. Each part was directed by a different team member thus the artistic style taken for each part is different. Each directors wrote, storyboarded and did the color script and backgrounds for their short stories, however the animation and post-production was split amongst the team members. The final product will be a 2D digitally animated, fully colored animation around 7 minutes.